Degradation of chloramphenicol and metronidazole by electro-Fenton process using graphene oxide-Fe3O4 as heterogeneous catalyst. Issue 2 (April 2019) - Görmez, Fatma; Görmez, Özkan; Gözmen, Belgin; Kalderis, Dimitrios
Highlights: A novel GO-Fe3 O4 composite catalyst was prepared and characterized. >99% degradation was achieved for both chloramphenicol and metronidazole. Degradation kinetics for both substances were determined as first-order. Oxalic and glyoxylic acid were the main recalcitrant by-products identified. The composite showed minimum Fe leaching and was still effective after 4 treatment cycles. Abstract: This study investigates the degradation and mineralization of two widely used antibiotics, chloramphenicol and metronidazole, by an electro-Fenton process using graphene oxide-Fe3 O4 as a heterogeneous catalyst. The graphene oxide-Fe3 O4 composite was typically characterized through conventional spectroscopic and surface analytical methods. The effects of treatment time, pH, catalyst concentration and applied current were examined. In the absence of the graphene oxide-Fe3 O4 catalyst (homogeneous environment), the optimum mineralization rates obtained were 57 and 71% at pH 3 and 300 min treatment time for metronidazole and chloramphenicol solutions, respectively. When the optimum graphene oxide-Fe3 O4 concentration of 0.5 g L −1 was used, mineralization rates of 73 and 86% were achieved respectively, at the same conditions. This indicated the efficiency of the catalyst and proved that the heterogeneous electro-Fenton process was more effective compared to the homogenous electro-Fenton process. At the same conditions, degradation of chloramphenicol and metronidazole was >99%. The difference between the near-complete antibiotic degradation and the lower mineralization rates, can be justified by the presence of persistent by-products, such as oxalic and glyoxylic acid. Finally, the prepared catalyst showed high levels of reusability and its performance remained practically the same after 4 electro-Fenton runs.